Trophic connections between Calanus spp. and deep-sea benthos in the Fram Strait, Arctic Ocean - Dewi Ford; Katrin Linse; Sabena Jane Blackbird; Anna K. Wadsworth; Jennifer J. Freer; Rachel Jeffreys; Lydia Anastasia Schmidt; Daniel J. Mayor (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Discovery of a bathyal methane seep field at the north-western Vestnesa Ridge, Fram Strait - Katrin Linse; Lilian Boehringer; Saskia Brix; Jennifer Dannheim; Jonas Hagemann; Fereshteh Hemmateenejad; Áki Jarl Láruson; Giuliana Panieri; Lydia Anastasia Schmidt; Maximilian Schrade; Carolin Uhlir; Autun Purser (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Rich to ridges—diversity and composition of benthic Isopoda along a bathymetric gradient from shelf to abyss in the Nordic Seas - Stefanie Kaiser; Saskia Brix; Andrea Desiderato; Moana Kolb; Karlotta Kürzel; Anne Helene S. Tandberg; Katrin Linse (Marine Biodiversity, 2026)

Unpouching Peracarida relationships with ultraconserved elements - Tammy Iwasa-Arai; Katrin Linse; Sónia C.S. Andrade; Gonzalo Giribet (Molecular Phylogenetics and Evolution, 2026)

Clinging onto Arctic Benthos: Biogeography of Amathillopsis spinigera Heller, 1875 (Crustacea: Amphipoda), including its redescription - Saskia Brix; Thea Sophie Elsig; Patricia Esquete; Áki Jarl Láruson; Katrin Linse; Elisabeth Schaal; Lydia Anastasia Schmidt; Carolin Uhlir; Johanna N.J. Weston; Anne-Nina Lörz (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

The abundance, diversity, and assemblage structure of the macrobenthos at the South Georgia shelf methane seeps - Madeline P. B. C. Anderson; William D. K. Reid; Gerhard Bohrmann; Ingrid Dohrmann; Philip R. Hollyman; Sabine Kasten; Thomas Pape; Miriam Römer; Jason Newton; Ben D. Wigham; Katrin Linse (Frontiers in Marine Science, 2025)
A quarter of all marine methane, a potent greenhouse gas, is estimated to be hosted in Southern Ocean sediments. Climate change-induced ocean warming and ice shelf melting risk the stability of sedimentary gas hydrates, resulting in potential degassing and establishment of marine methane seeps. While methane seeps can originate from various sources, the destabilisation of gas hydrates may contribute to the formation and persistence of some active seeps. The impact of these seeps and their risks to the diverse sub-Antarctic and Antarctic benthic shelf fauna is uncertain. As a sentinel for change in the sub-Antarctic and wider Antarctic region, this study explores South Georgia’s continental shelf macrobenthic methane seep assemblages, for their diversity, richness, and abundance, and their environmental drivers influencing macrofaunal community composition. Seven of South Georgia’s shelf troughs hosting active methane seeps were investigated during RV METEOR’s M134 expedition in 2017. Species richness at 11 stations ranged from 19–51 species from a total of 103 species discovered across all sites. Station abundance ranged from 3,303–30,326 m². Diversity was higher at stations with greater methane- and sulfate-flux, and hydrogen sulfide at 25 cm depth. Abundance and richness were lower where surface sediment had high hydrogen sulfide concentrations. Abundance and species richness were lower at stations dominated by iron-reduction in the sediment. Assemblages were characterized by the presence of Southern Ocean species and by the absence of megafaunal chemosynthetic taxa. Arthropods, mostly crustacean, and annelid species made up three quarters of overall species richness, while molluscan and echinoderm species were depauperate with only 15 species. Compared with Southern Ocean macrobenthic assemblages, the South Georgia seep assemblages from sediments with gas hydrates present in the near-surface showed a lower species richness and change in taxon composition, also accompanied by lower numbers of calcium-carbonate shell bearing taxa. The current diverse benthic Antarctic biodiversity, especially the diversity of calcifiers, is likely at risk when methane seeps become established on Southern Ocean continental shelves as the reduction in habitat diversity leads to the decline in taxonomic diversity and species richness.

Circumpolar and Regional Seascape Drivers of Genomic Variation in a Southern Ocean Octopus - Sally C. Y. Lau; Nerida G. Wilson; Phillip C. Watts; Catarina N. S. Silva; Ira R. Cooke; A. Louise Allcock; Felix C. Mark; Katrin Linse; Toni Jernfors; Jan M. Strugnell (Molecular Ecology, 2025)
Understanding how ecological, environmental and geographic features influence population genetic patterns provides crucial insights into a species' evolutionary history, as well as their vulnerability or resilience under climate change. In the Southern Ocean, population genetic variation is influenced across multiple spatial scales ranging from circum‐Antarctic, which encompasses the entire continent, to regional, with varying levels of geographic separation. However, comprehensive analyses testing the relative importance of different environmental and geographic variables on genomic variation across these scales are generally lacking in the Southern Ocean. Here, we examine genome‐wide single nucleotide polymorphisms of the Southern Ocean octopus Pareledone turqueti across the Scotia Sea and the Antarctic continental shelf, at depths between 102 and 1342 m, throughout most of this species' range. The circumpolar distribution of P. turqueti is biogeographically structured with a clear signature of isolation‐by‐geographical distance, but with long‐distance genetic connectivity also detected between East and West Antarctica. Genomic variation of P. turqueti was also associated with bottom water temperature at a circumpolar scale, driven by a genotype‐temperature association with the warmer sub‐Antarctic Shag Rocks and South Georgia. Within the Scotia Sea, geographic distance, oxygen and fine‐scale isolation‐by‐water depth were apparent drivers of genomic variation at regional scales. Putative positive selection of haemocyanin (oxygen transport protein), calcium ion transport and genes linked to RNA modification, detected within the Scotia Sea, suggest physiological adaptation to the regional sharp temperature gradient (~0–+2°C). Overall, we identified seascape drivers of genomic variation in the Southern Ocean at circumpolar and regional scales in P. turqueti and contextualised the role of environmental adaptations in the Southern Ocean.

A new species of Fissidentalium (Scaphopoda: Dentaliidae) in association with an actinostolid anemone from the abyssal Labrador Sea - Katrin Linse; Jenny Neuhaus (Marine Biodiversity, 2024)
The benthic biodiversity of the abyssal Labrador Sea was investigated using Agassiz trawl and in situ imagery. A megafaunal scaphopod associated with an epizoic anemone was recovered from soft sediments. Morphological and molecular investigations revealed the scaphopod to be an undescribed species in the dentaliid genus Fissidentalium P. Fischer, 1885. The new scaphopod species is characterised by a large size for the genus, is moderately curved, with numerous narrow, longitudinal ribs (60 ribs at 11 mm diameter ventral aperture), a dentaliid radula, and is described herein as Fissidentalium aurae sp. nov. The new species shows a close genetic relationship to congeners of Fissidentalium and separates from the sister genera Dentalium Linnaeus, 1758 and Antalis H. Adams & A. Adams, 1854. Genetic COI barcoding of the epizoic anemone suggests the species is a member of the family Actinostolidae Carlgren, 1932. The discovered association of a burrowing scaphopod with an epifaunal anemone at abyssal depth is a new record for the region and is indicative of how little is known about symbioses in the deep sea.

Phylogenomic analyses reveal a single deep-water colonisation in Patellogastropoda - Ying Qi; Zhaoyan Zhong; Xu Liu; Xing He; Yadong Zhou; Lili Zhang; Chong Chen; Katrin Linse; Jian-Wen Qiu; Jin Sun (Molecular Phylogenetics and Evolution, 2024)

Macrobenthic Mollusca of the Prince Gustav Channel, Eastern Antarctic Peninsula: An Area Undergoing Colonisation - Madeline P. B. C. Anderson; Phillip B. Fenberg; Huw J. Griffiths; Katrin Linse (Frontiers in Marine Science, 2021)
In 2018 RRS James Clark Ross investigated the marine benthic biodiversity of the Prince Gustav Channel area which separates the eastern coast of the Antarctic Peninsula from James Ross Island. The southern end of this channel had been covered by the Prince Gustav Ice Shelf until its collapse in 1995. Benthic samples were collected by an epibenthic sledge at six stations (200–1,200 m depth) in the channel and adjacent Duse Bay. In total 20,307 live collected mollusc specimens belonging to 50 species and 4 classes (Solenogastres, Bivalvia, Gastropoda, and Scaphopoda) were identified. The area may be characterised by it’s low species richness (ranging from 7 to 39 species per station) but high abundances (specifically of the Scaphopods with 11,331 specimens). The functional traits of the community were dominated by motile development and mobility type. Assemblage analyses of the molluscan species abundances within the Prince Gustav Channel stations sit distinct, with no pattern by depth or location. However, when bivalve assemblages were analysed with reference to the wider Weddell Gyre region (15 stations from 300 to 2,000 m depth), the Prince Gustav Channel sits distinct from the other Weddell Gyre stations with a higher dissimilarity between the deeper or more geographically distant areas. The Prince Gustav Channel is undergoing colonisation following the recent ice shelf collapse. With many Antarctic ice shelves threatened under climate warming, this area, with future monitoring, may serve as a case study of benthic faunal succession.

Editorial: Effects of Ice Loss on Marine Biodiversity - Katrin Linse; Ilka Peeken; Anne Helene Solberg Tandberg (Frontiers in Marine Science, 2021)

The Discovery and Preliminary Geological and Faunal Descriptions of Three New Steinahóll Vent Sites, Reykjanes Ridge, Iceland - James Taylor; Colin Devey; Morgane Le Saout; Sven Petersen; Tom Kwasnitschka; Inmaculada Frutos; Katrin Linse; Anne-Nina Lörz; Dominik Pałgan; Anne H. Tandberg; Jörundur Svavarsson; Daniel Thorhallsson; et al. (Frontiers in Marine Science, 2021)
During RV MS Merian expedition MSM75, an international, multidisciplinary team explored the Reykjanes Ridge from June to August 2018. The first area of study, Steinahóll (150–350 m depth), was chosen based on previous seismic data indicating hydrothermal activity. The sampling strategy included ship- and AUV-mounted multibeam surveys, Remotely Operated Vehicle (ROV), Epibenthic Sledge (EBS), and van Veen grab (vV) deployments. Upon returning to Steinahóll during the final days of MSM75, hydrothermal vent sites were discovered using the ROV Phoca (Kiel, GEOMAR). Here we describe and name three new, distinct hydrothermal vent site vulnerable marine ecosystems (VMEs); Hafgufa, Stökkull, Lyngbakr. The hydrothermal vent sites consisted of multiple anhydrite chimneys with large quantities of bacterial mats visible. The largest of the three sites (Hafgufa) was mapped, and reconstructed in 3D. In total 23,310 individual biological specimens were sampled comprising 41 higher taxa. Unique fauna located in the hydrothermally venting areas included two putative new species of harpacticoid copepod ( Tisbe sp. nov. and Amphiascus sp. nov.), as well as the sponge Lycopodina cupressiformis (Carter, 1874). Capitellidae Grube, 1862 and Dorvilleidae Chamberlin, 1919 families dominated hydrothermally influenced samples for polychaetes. Around the hydrothermally influenced sites we observed a notable lack of megafauna, with only a few species being present. While we observed hydrothermal associations, the overall species composition is very similar to that seen at other shallow water vent sites in the north of Iceland, such as the Mohns Ridge vent fields, particularly with peracarid crustaceans. We therefore conclude the community overall reflects the usual “background” fauna of Iceland rather than consisting of “vent endemic” communities as is observed in deeper vent systems, with a few opportunistic species capable of utilizing this specialist environment.

Corrigendum: Marine Genetic Resources in Areas Beyond National Jurisdiction: Promoting Marine Scientific Research and Enabling Equitable Benefit Sharing - Alex D. Rogers; Amy Baco; Elva Escobar-Briones; Duncan Currie; Kristina Gjerde; Judith Gobin; Marcel Jaspars; Lisa Levin; Katrin Linse; Muriel Rabone; Eva Ramirez-Llodra; Javier Sellanes; et al. (Frontiers in Marine Science, 2021)

Marine Genetic Resources in Areas Beyond National Jurisdiction: Promoting Marine Scientific Research and Enabling Equitable Benefit Sharing - Alex D. Rogers; Amy Baco; Elva Escobar-Briones; Duncan Currie; Kristina Gjerde; Judith Gobin; Marcel Jaspars; Lisa Levin; Katrin Linse; Muriel Rabone; Eva Ramirez-Llodra; Javier Sellanes; et al. (Frontiers in Marine Science, 2021)
Growing human activity in areas beyond national jurisdiction (ABNJ) is driving increasing impacts on the biodiversity of this vast area of the ocean. As a result, the United Nations General Assembly committed to convening a series of intergovernmental conferences (IGCs) to develop an international legally-binding instrument (ILBI) for the conservation and sustainable use of marine biological diversity of ABNJ [the biodiversity beyond national jurisdiction (BBNJ) agreement] under the United Nations Convention on the Law of the Sea. The BBNJ agreement includes consideration of marine genetic resources (MGR) in ABNJ, including how to share benefits and promote marine scientific research whilst building capacity of developing states in science and technology. Three IGCs have been completed to date with the fourth delayed by the Covid pandemic. This delay has allowed a series of informal dialogues to take place between state parties, which have highlighted a number of areas related to MGR and benefit sharing that require technical guidance from ocean experts. These include: guiding principles on the access and use of MGR from ABNJ; the sharing of knowledge arising from research on MGR in ABNJ; and capacity building and technology transfer for developing states. In this paper, we explain what MGR are, the methods required to collect, study and archive them, including data arising from scientific investigation. We also explore the practical requirements of access by developing countries to scientific cruises, including the sharing of data, as well as participation in research and development on shore whilst promoting rather than hindering marine scientific research. We outline existing infrastructure and shared resources that facilitate access, research, development, and benefit sharing of MGR from ABNJ; and discuss existing gaps. We examine international capacity development and technology transfer schemes that might facilitate or complement non-monetary benefit sharing activities. We end the paper by highlighting what the ILBI can achieve in terms of access, utilization, and benefit sharing of MGR and how we might future-proof the BBNJ Agreement with respect to developments in science and technology.

Breaking All the Rules: The First Recorded Hard Substrate Sessile Benthic Community Far Beneath an Antarctic Ice Shelf - Huw J. Griffiths; Paul Anker; Katrin Linse; Jamie Maxwell; Alexandra L. Post; Craig Stevens; Slawek Tulaczyk; James A. Smith (Frontiers in Marine Science, 2021)
The seafloor beneath floating ice shelves accounts roughly a third of the Antarctic’s 5 million km 2 of continental shelf. Prior to this study, our knowledge of these habitats and the life they support was restricted to what has been observed from eight boreholes drilled for geological and glaciological studies. The established theory of sub-ice shelf biogeography is that both functional and taxonomic diversities decrease along a nutrient gradient with distance from the ice shelf front, resulting in a depauperate fauna, dominated by mobile scavengers and predators toward the grounding line. Mobile macro-benthic life and mega-benthic life have been observed as far as 700 km under an ice shelf. New observations from two boreholes in the Filchner-Ronne Ice Shelf challenge the idea that sessile organisms reduce in prevalence the further under the ice you go. The discovery of an established community consisting of only sessile, probably filter feeding, organisms (sponges and other taxa) on a boulder 260 km from the ice front raises significant questions, especially when the local currents suggest that this community is somewhere between 625 km and 1500 km in the direction of water flow from the nearest region of photosynthesis. This new evidence requires us to rethink our ideas with regard to the diversity of community types found under ice shelves, the key factors which control their distribution and their vulnerability to environmental change and ice shelf collapse.

In-situ Image Analysis of Habitat Heterogeneity and Benthic Biodiversity in the Prince Gustav Channel, Eastern Antarctic Peninsula - Peter M. Almond; Katrin Linse; Simon Dreutter; Susie M. Grant; Huw J. Griffiths; Rowan J. Whittle; Melanie Mackenzie; William D. K. Reid (Frontiers in Marine Science, 2021)
Habitat heterogeneity is important for maintaining high levels of benthic biodiversity. The Prince Gustav Channel, on the Eastern Antarctic Peninsula, is characterized by an array of habitat types, ranging from flat, mud-dominated sheltered bays to steep and rocky exposed slopes. The channel has undergone dramatic environmental changes in recent decades, with the southern end of the channel permanently covered by the Prince Gustav Ice Shelf until it completely collapsed in 1995. Until now the marine benthic fauna of the Prince Gustav Channel has remained unstudied. A shallow underwater camera system and Agassiz trawl were deployed at different locations across the channel to collect information on habitat type and heterogeneity, benthic community composition and macrofaunal biomass. The texture of the seafloor was found to have a significant influence on the benthos, with hard substrates supporting higher abundances and diversity. Suspension and filter feeding organisms, including porifera, crinoids, and anthozoans, were strongly associated with hard substrates, with the same being true for deposit feeders, such as holothurians, and soft sediments. Habitat heterogeneity was high across the Prince Gustav Channel, particularly on a local scale, and this was significant in determining patterns of benthic composition and abundance. Other physical variables including depth and seafloor gradient played significant, interactive roles in determining composition potentially mediated through other processes. Sites that were once covered by the Prince Gustav Ice Shelf held distinct and unique communities, suggesting that the legacy of the ice shelf collapse may still be reflected in the benthos. Biomass estimations suggest that critical thresholds of vulnerable marine ecosystem indicator taxa, as defined by the Commission for the Conservation of Antarctic Marine Living Resources, have been met at multiple locations within the Prince Gustav Channel, which has implications for the future establishment of no take zones and marine protected areas within the region.

Annelid Fauna of the Prince Gustav Channel, a Previously Ice-Covered Seaway on the Northeastern Antarctic Peninsula - Regan Drennan; Thomas G. Dahlgren; Katrin Linse; Adrian G. Glover (Frontiers in Marine Science, 2021)
The Prince Gustav Channel is a narrow seaway located in the western Weddell Sea on the northeastern-most tip of the Antarctic Peninsula. The channel is notable for both its deep (>1200 m) basins, and a dynamic glacial history that most recently includes the break-up of the Prince Gustav Ice Shelf, which covered the southern portion of the channel until its collapse in 1995. However, the channel remains mostly unsampled, with very little known about its benthic biology. We present a preliminary account of the benthic annelid fauna of the Prince Gustav Channel in addition to samples from Duse Bay, a sheltered, glacier-influenced embayment in the northwestern portion of the channel. Samples were collected using an Agassiz Trawl, targeting megafaunal and large macrofaunal sized animals at depths ranging between 200–1200 m; the seafloor and associated fauna were also documented in situ using a Shallow Underwater Camera System (SUCS). Sample sites varied in terms of depth, substrate type, and current regime, and communities were locally variable across sites in terms of richness, abundance, and both taxonomic and functional composition. The most diverse family included the motile predator/scavenger Polynoidae, with 105 individuals in at least 12 morphospecies, primarily from a single site. This study provides first insights into diverse and spatially heterogeneous benthic communities in a dynamic habitat with continuing glacial influence, filling sampling gaps in a poorly studied region of the Southern Ocean at direct risk from climate change. These specimens will also be utilized in future molecular investigations, both in terms of describing the genetic biodiversity of this site and as part of wider phylogeographic and population genetic analyses assessing the connectivity, evolutionary origins, and demographic history of annelid fauna in the region.

Abundance and Distributional Patterns of Benthic Peracarid Crustaceans From the Atlantic Sector of the Southern Ocean and Weddell Sea - Davide Di Franco; Katrin Linse; Huw J. Griffiths; Christian Haas; Hanieh Saeedi; Angelika Brandt (Frontiers in Marine Science, 2020)

Ecophysiology and ecological limits of symbiotrophic vesicomyid bivalves (Pliocardiinae) in the Southern Ocean - Katrin Linse; Julia D. Sigwart; Chong Chen; Elena M. Krylova (Polar Biology, 2020)
Geothermal energy provides an important resource in Antarctic marine ecosystems, exemplified by the recent discovery of large-sized chemosymbiotic vesicomyid bivalves (subfamily Pliocardiinae) in the Southern Ocean. These clams, which we identified as Archivesica s.l. puertodeseadoi, have been reported as dead shells in areas previously covered by Larsen A and B ice shelves (eastern Antarctic Peninsula) and as live animals from active hydrothermal sites in the Kemp Caldera (South Sandwich Arc) at depths of 852–1487 m. Before, A . puertodeseadoi was known only from its type locality in the Argentine Sea, so we considerably extend the range of the species. Observations taken by remotely operated vehicle (ROV) footage show that the clams can live buried in sediment, or epilithically on the surface of rocks in diffuse geothermal flow. Experimental respirometry was conducted at surface pressure on individual bivalves acclimated to either their habitat temperature (4 °C) or elevated temperature (10 °C). The range of standard metabolic rates, from 3.13 to 6.59 (MO 2 , μmol O 2 h −1 g −1 dry tissue mass), is similar to rates measured ex situ for other species in this clade, and rates did not differ significantly between temperature groups. Taken together, these data indicate a range of ecophysiological flexibility for A. puertodeseadoi . Although adapted to a specialist mode of life, this bivalve exploits a relatively broad range of habitats in the Southern Ocean: within sulphidic sediments, epilithically in the presence of diffuse sulphidic flow, or in deep methane-enriched seawater trapped under ice.

Eualus amandae (Decapoda: Caridea: Thoridae) is an indicator of active venting sites in the Southern Ocean - Katrin Linse; Gerhard Bohrmann; Julia Sigwart (Marine Biodiversity, 2019)

A new trochoidean gastropod (Vetigastropoda: Skeneidae) discovered from deep-sea hydrothermal vents in the Southern Ocean - Chong Chen; Katrin Linse (Marine Biodiversity, 2019)

sFDvent: A global trait database for deep‐sea hydrothermal‐vent fauna - Abbie S. A. Chapman; Stace E. Beaulieu; Ana Colaço; Andrey V. Gebruk; Ana Hilario; Terue C. Kihara; Eva Ramirez‐Llodra; Jozée Sarrazin; Verena Tunnicliffe; Diva J. Amon; Maria C. Baker; Rachel E. Boschen‐Rose; et al. (Global Ecology and Biogeography, 2019)
Motivation Traits are increasingly being used to quantify global biodiversity patterns, with trait databases growing in size and number, across diverse taxa. Despite growing interest in a trait‐based approach to the biodiversity of the deep sea, where the impacts of human activities (including seabed mining) accelerate, there is no single repository for species traits for deep‐sea chemosynthesis‐based ecosystems, including hydrothermal vents. Using an international, collaborative approach, we have compiled the first global‐scale trait database for deep‐sea hydrothermal‐vent fauna – sFDvent ( s Div‐funded trait database for the F unctional D iversity of vent s). We formed a funded working group to select traits appropriate to: (a) capture the performance of vent species and their influence on ecosystem processes, and (b) compare trait‐based diversity in different ecosystems. Forty contributors, representing expertise across most known hydrothermal‐vent systems and taxa, scored species traits using online collaborative tools and shared workspaces. Here, we characterise the sFDvent database, describe our approach, and evaluate its scope. Finally, we compare the sFDvent database to similar databases from shallow‐marine and terrestrial ecosystems to highlight how the sFDvent database can inform cross‐ecosystem comparisons. We also make the sFDvent database publicly available online by assigning a persistent, unique DOI. Main types of variable contained Six hundred and forty‐six vent species names, associated location information (33 regions), and scores for 13 traits (in categories: community structure, generalist/specialist, geographic distribution, habitat use, life history, mobility, species associations, symbiont, and trophic structure). Contributor IDs, certainty scores, and references are also provided. Spatial location and grain Global coverage (grain size: ocean basin), spanning eight ocean basins, including vents on 12 mid‐ocean ridges and 6 back‐arc spreading centres. Time period and grain sFDvent includes information on deep‐sea vent species, and associated taxonomic updates, since they were first discovered in 1977. Time is not recorded. The database will be updated every 5 years. Major taxa and level of measurement Deep‐sea hydrothermal‐vent fauna with species‐level identification present or in progress. Software format .csv and MS Excel (.xlsx).

A New Vent Limpet in the Genus Lepetodrilus (Gastropoda: Lepetodrilidae) From Southern Ocean Hydrothermal Vent Fields Showing High Phenotypic Plasticity - Katrin Linse; Christopher Nicolai Roterman; Chong Chen (Frontiers in Marine Science, 2019)

A Multidisciplinary Approach for Generating Globally Consistent Data on Mesophotic, Deep-Pelagic, and Bathyal Biological Communities - Lucy Woodall; Dominic Andradi-Brown; Andrew Brierley; Malcolm Clark; Douglas Connelly; Rob Hall; Kerry Howell; Veerle Huvenne; Katrin Linse; Rebecca Ross; Paul Snelgrove; Paris Stefanoudis; et al. (Oceanography, 2018)

Hydrological features above a Southern Ocean seamount inhibit larval dispersal and promote speciation: evidence from the bathyal mytilid Dacrydium alleni sp. nov. (Mytilidae: Bivalvia) - Mark A. Beeston; Simon M. Cragg; Katrin Linse (Polar Biology, 2018)

Comparative marine biodiversity and depth zonation in the Southern Ocean: evidence from a new large polychaete dataset from Scotia and Amundsen seas - Lenka Neal; Katrin Linse; Madeleine J. Brasier; Emma Sherlock; Adrian G. Glover (Marine Biodiversity, 2018)

Distributional Patterns of Polychaetes Across the West Antarctic Based on DNA Barcoding and Particle Tracking Analyses - Madeleine J. Brasier; James Harle; Helena Wiklund; Rachel M. Jeffreys; Katrin Linse; Henry A. Ruhl; Adrian G. Glover (Frontiers in Marine Science, 2017)

Bacterial communities associated with the Southern Ocean vent gastropod, Gigantopelta chessoia: indication of horizontal symbiont transfer - Jane L. Heywood; Chong Chen; David A. Pearce; Katrin Linse (Polar Biology, 2017)

Low connectivity between ‘scaly-foot gastropod’ (Mollusca: Peltospiridae) populations at hydrothermal vents on the Southwest Indian Ridge and the Central Indian Ridge - Chong Chen; Jonathan T. Copley; Katrin Linse; Alex D. Rogers (Organisms Diversity & Evolution, 2015)

Reproductive morphology of the deep-sea protobranch bivalves Yoldiella ecaudata, Yoldiella sabrina, and Yoldiella valettei (Yoldiidae) from the Southern Ocean - Adam J. Reed; James P. Morris; Katrin Linse; Sven Thatje (Polar Biology, 2014)

Diversity, abundance and composition in macrofaunal molluscs from the Ross Sea (Antarctica): results of fine-mesh sampling along a latitudinal gradient - Stefano Schiaparelli; Claudio Ghiglione; Maria Chiara Alvaro; Huw J. Griffiths; Katrin Linse (Polar Biology, 2014)

The Early Miocene Cape Melville Formation fossil assemblage and the evolution of modern Antarctic marine communities - Rowan J. Whittle; Fernanda Quaglio; Huw J. Griffiths; Katrin Linse; J. Alistair Crame (The Science of Nature, 2014)

An unusual hermaphrodite reproductive trait in the Antarctic brooding bivalve Lissarca miliaris (Philobryidae) from the Scotia Sea, Southern Ocean - Adam J. Reed; Sven Thatje; Katrin Linse (Polar Biology, 2013)

High genetic diversity within Epimeria georgiana (Amphipoda) from the southern Scotia Arc - Anne-Nina Lörz; Peter Smith; Katrin Linse; Dirk Steinke (Marine Biodiversity, 2012)

Antarctic DNA barcoding; a drop in the ocean? - Rachel A. Grant; Huw J. Griffiths; Dirk Steinke; Victoria Wadley; Katrin Linse (Polar Biology, 2011)

Barcoding Antarctic Biodiversity: current status and the CAML initiative, a case study of marine invertebrates - Rachel Anne Grant; Katrin Linse (Polar Biology, 2009)

Marine, intertidal, freshwater and terrestrial biodiversity of an isolated polar archipelago - David K. A. Barnes; Stefanie Kaiser; Huw J. Griffiths; Katrin Linse (Journal of Biogeography, 2009)
Aim We ask how biodiverse is a polar archipelago; how this faunal richness is spread across marine, intertidal, freshwater, terrestrial and parasitic realms; and how fast species are accumulated with increased sampling effort. Location The South Orkney Islands (SOI), Scotia Arc, Southern Ocean. Methods We sampled mega‐ and macro‐benthos at the SOI using scuba in the shallows (0–10 m), a rough bottom otter trawl at 150–250 m and an Agassiz trawl and epibenthic sledge, both at depths of 200, 500, 1000 and 1500 m. We also collated species occurrence at the SOI in each realm from a century of literature and modern databases to investigate patterns in species accumulation, endemism, faunistic affinities and bathymetric ranges in three model taxa. Results Our 11 benthic samples showed that point biodiversity at the SOI is high, yielding 19 classes and 158 species. Nearly a third were new to the area, whilst five species and one genus were new to science. The shallowest samples were richest but had fewest new records of species. Known richness at the SOI is dominated by marine species (1026), of which 821 (83.3%) were benthic. Across all realms, 1224 species (50 classes, 24 phyla) were recorded, of which 43 were intertidal, 64 freshwater, 100 terrestrial, 60 parasitic and 40 birds. Species accumulation curves for model taxa showed new sampling yields about 0.75% per sample of known benthic richness, so by Antarctic standards we know the SOI quite well. Most species are Southern Ocean endemics, but very few occur only at the SOI. Main conclusions This first estimate of faunal biodiversity of a polar locality demonstrates both high richness and high levels of knowledge at the SOI. As suspected but never quantified, the benthos dominates polar biodiversity, at least at the SOI. Marine species there constitute 20% of those recently listed for the entire Southern Ocean, whilst > 60% of terrestrial species are known from Antarctica. The SOI, being one of the better‐studied polar locations, of known age and with a discrete shelf, represent an important source of comparison for biodiversity studies. Our data clearly show that richness and our knowledge of the polar fauna differ across environments.

Towards a generalized biogeography of the Southern Ocean benthos - Huw J. Griffiths; David K. A. Barnes; Katrin Linse (Journal of Biogeography, 2009)
Aim To investigate whether the biogeographical regions proposed by J. W. Hedgpeth and widely adopted by other authors hold true, are an oversimplification or with further data might show a unified Antarctic province. Location Southern Hemisphere. Methods The distributions of 1318 species of bivalves, 4656 species of gastropods, 1465 species of cheilostome and 167 species of cyclostome bryozoans were analysed for 29 regions in the Southern Hemisphere, including South American, South African, Tasmanian, New Zealand, sub‐Antarctic and Antarctic regions. We present data on species richness, rates of endemism, patterns of radiation, faunal similarities and multivariate biogeographical analyses. Results The most striking pattern to emerge from our data set of species counts per region was a strong east–west hemispheric asymmetry, with high species numbers in New Zealand, Tasmania and South Africa and low numbers in South America. In contrast, no difference was found in richness between the east and west parts of the Southern Ocean. We compared findings in our model taxa with published data on ascidians, cephalopods and pycnogonids. Further evidence of strong faunal links between the Antarctic and South America is reported in this study, although we found little evidence for a biogeographical relationship between the Antarctic or South America and New Zealand/Tasmania. Strong evidence exists for a long‐term influence of the Antarctic Circumpolar Current upon the distribution of Southern Ocean benthos. This is demonstrated by the reduced prevalence of South American species in the Antarctic and sub‐Antarctic with increasing distance from South America in the direction of the current. Three of our four study taxa (bivalves, cheilostomes and cyclostomes) show the Southern Ocean as a ‘single functional unit’ with no evidence for a biogeographical split between east and west. Main conclusions Unlike the biogeographical schemes previously proposed, we show that biogeographical regions in the Southern Ocean differ depending upon the class of animals being considered. Despite this we suggest that some general rules are viable, including species endemism rates of around 50%, a single Antarctic province and a definite distinction between the sub‐Antarctic islands influenced by South America and those of New Zealand.

Diversity and species distribution of polychaetes, isopods and bivalves in the Atlantic sector of the deep Southern Ocean - Kari E. Ellingsen; Angelika Brandt; Brigitte Ebbe; Katrin Linse (Polar Biology, 2007)

Is the Scotia Sea a centre of Antarctic marine diversification? Some evidence of cryptic speciation in the circum-Antarctic bivalve Lissarca notorcadensis (Arcoidea: Philobryidae) - Katrin Linse; Therese Cope; Anne-Nina Lörz; Chester Sands (Polar Biology, 2007)

Growth rate and its variability in erect Antarctic bryozoans - David K. A. Barnes; Karen E. Webb; Katrin Linse (Polar Biology, 2007)

Review on the distribution and biology of Antarctic Monoplacophora, with first abyssal record of Laevipilina antarctica - Michael Schrödl; Katrin Linse; Enrico Schwabe (Polar Biology, 2006)

Shallow benthic fauna communities of South Georgia Island - David K. A. Barnes; Katrin Linse; Cath Waller; Simon Morely; Peter Enderlein; Keiron P. P. Fraser; Matt Brown (Polar Biology, 2006)

Missing link in the Southern Ocean: sampling the marine benthic fauna of remote Bouvet Island - Wolf E. Arntz; Sven Thatje; Katrin Linse; Conxita Avila; Manuel Ballesteros; David K. A. Barnes; Thérèse Cope; Francisco J. Cristobo; Claude de Broyer; Julian Gutt; Enrique Isla; Pablo López-González; et al. (Polar Biology, 2006)

New records of shelled marine molluscs at Bouvet Island and preliminary assessment of their biogeographic affinities - Katrin Linse (Polar Biology, 2006)

More evidence of speciation and dispersal across the Antarctic Polar Front through molecular systematics of Southern Ocean Limatula (Bivalvia: Limidae) - Timothy J. Page; Katrin Linse (Polar Biology, 2002)

Abundance and diversity of peracarid taxa (Crustacea, Malacostraca) along a transect through the Beagle Channel, Patagonia - Angelika Brandt; Katrin Linse; Ursula Weber (Polar Biology, 1997)